DESIGN OF WATER GUAVA FRUIT PICKER USING OWAS METHOD - Yudhistira, Arga Sri; Prihastono, Endro; Radyanto, Mohammad Riza (Proceeding SENDI_U, 2019)
Water guava is one of the fruits that is often found and is a typical fruit from Demak Regency. Many farmers in this city prefer to plant water guava from other fruits. The large potential of plantations in the city is interesting for our research material. This study aims to design fruit pickers using the Ovako Working Posture Analysis System (OWAS) method to assist the process of harvesting guava, and to make it easier for farmers not to climb trees and not damage guava fruit that has not been harvested. In addition, by climbing trees, allowing injury and disturbing the musculoskeletal system. Using this developed tool there has been an increase in production capacity where by using old tools, each harvest only gets 24 pieces / minute / tree, while using a new fruit picking tool produces 34 pieces / minute / tree or an increase of 42% Key Word: Water Guava, Fruit Picker, OWAS Method, Musculoskeletal Injury